Developing Assessment Instrument on Writing on Descriptive Paragraph Based on Picture of Junior High School Students - Santi, Elia; Haris Setiawan, M.; Khumaedi, Muhammad (Journal of Research and Educational Research Evaluation, 2019)
This research is motivated by the absence of writing assessment instruments on descriptive material based on picture, especially students of class VIII. The writing assessment instruments on paragraph descriptive material based on the picture used are still holistic. This study aims to develop Writing assessment instruments on Descriptive Material Based on Middle School Class VIII Students. The method used is instrument development research with 9 development steps. Content validation by experts was analyzed using the Aiken formula, the reliability of the experts was analyzed using Two way ANOVA and analyzed using the Hoyt formula. The construct validity was analyzed using Exploratory Factor Analysis (EFA) analysis. The results of the development research show that the validity of writing appraisal content instruments on descriptive material based on picture specially students of class VIII through Expert Judgment produces a reliability coefficient of> 0.3, meaning that it can be said that writing appraisal on descriptive material has high validity. Also, the reliability results of the instrument using interrater with the Hoyt formula showed that 0.89. Analysis of the data in the field trials can be seen in the KMO which shows a KMO value> 0.5 which means that the instrument indicators can be further analyzed. In writing assessment produces component factors that are formed and can represent all indicators. The factors are the main ideas, organization, and mechanic. While the reliability obtained a coefficient> 0.5 which means that the writing assessment has good reliability. Based on the results of the study, it is recommended that all lecturers, teachers and other educators use valid and reliable instruments. Thank you to all the teams especially the lecturers who have given good direction and participation so that this journal can give best contributes in theory and practice.